Indicator Species and Diversity in Mangroves at Darunu Mangrove Park - Mahmud, Maudy Rusmini; Rumengan, Antonius; Paruntu, Carolus Paulus; Schaduw, Joshian Nicolas William; Rumampuk, Natalie Detty C.; Warouw, Veibe (Sam Ratulangi University, 2025)
Mangrove ecosystems play a crucial role in maintaining the ecological balance of coastal areas, including protection against abrasion, providing habitat for marine species, and acting as a carbon sink. This study aims to identify indicator species and analyze biodiversity in Darunu Mangrove Park, Darunu Village, Wori Subdistrict, North Minahasa Regency. The research was conducted over three months (May–July 2024) using a line transect method for vegetation data collection. The results show that three dominant mangrove species were identified: Rhizophora apiculata, Rhizophora mucronata, and Sonneratia alba. R. mucronata exhibited significant dominance, both in terms of mature trees and saplings, and had the highest Important Value Index (IVI). The mangrove species diversity in this area is classified as low, with the. Diversity Index (H’) indicates an imbalance in the ecosystem's species composition. The Dominance Index (C) and Evenness Index (E) analyses indicate strong dominance by certain species, particularly R. mucronata. This study recommends the importance of enhanced monitoring and more intensive conservation efforts, including the replanting of threatened mangrove species and raising community awareness of mangrove ecosystem conservation. Keywords: Darunu Mangrove Park, Diversity, Indicator Species, Important Value Index. Abstrak Ekosistem mangrove memiliki peran penting dalam menjaga keseimbangan ekologi pesisir, meliputi perlindungan terhadap abrasi, penyedia habitat bagi spesies laut, dan sebagai penyerap karbon. Penelitian ini bertujuan untuk mengidentifikasi spesies indikator dan menganalisis keanekaragaman hayati di Darunu Mangrove Park, Desa Darunu, Kecamatan Wori, Kabupaten Minahasa Utara. Penelitian dilaksanakan selama tiga bulan (Mei-Juli 2024) dengan menggunakan metode transek garis untuk pengambilan data vegetasi. Hasil penelitian menunjukkan bahwa terdapat tiga jenis mangrove dominan, yaitu R. apiculata, R. mucronata, dan S. alba. Jenis R. mucronata menunjukkan dominasi yang signifikan, baik pada tingkat pohon maupun pancang, serta memiliki nilai Indeks Nilai Penting (INP) tertinggi. Keanekaragaman jenis mangrove di kawasan ini tergolong rendah dengan Indeks Keanekaragaman (H’) menunjukkan ketidakseimbangan spesies dalam ekosistem. Analisis Indeks Dominansi (C) dan Indeks Kemerataan (E) mengindikasikan adanya dominasi yang kuat dari beberapa spesies tertentu, terutama R. mucronata. Penelitian ini merekomendasikan pentingnya pemantauan dan upaya konservasi yang lebih intensif, termasuk penanaman kembali spesies mangrove yang terancam dan peningkatan kesadaran masyarakat terhadap pelestarian ekosistem mangrove. Kata kunci: Darunu Mangrove Park, Indeks Nilai Penting, Keanekaragaman, Spesies indicator